2015
DOI: 10.1097/01.asw.0000470371.77571.5d
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Ulcers in Older Adults

Abstract: The authors' data reported in the literature show that the prevalence of PrUs increases as an individual ages. The authors gathered data that showed a large area of intervention in managing the prevention of PrUs, such as an adequate use of protective aids, correcting malnutrition, and controlling incontinence. These results suggest that clinicians should focus more on the prevention of PrUs in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 34 publications
(24 reference statements)
2
26
0
3
Order By: Relevance
“…This study showed a low prevalence of pressure injuries in Austrian hospitals as compared with the prevalence of these injuries measured in other countries. Studies that assessed the prevalence of pressure injuries in similar European countries showed higher prevalence rates of up to 22% . An analysis of data collected in the US also shows higher prevalence rates of up to 20% .…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…This study showed a low prevalence of pressure injuries in Austrian hospitals as compared with the prevalence of these injuries measured in other countries. Studies that assessed the prevalence of pressure injuries in similar European countries showed higher prevalence rates of up to 22% . An analysis of data collected in the US also shows higher prevalence rates of up to 20% .…”
Section: Discussionmentioning
confidence: 92%
“…Pressure injuries represent a serious and complex health problem in older persons . As a result of geriatric syndromes such as incontinence, reduced mobility, or malnutrition, older persons in hospitals are at increased risk of developing a pressure injury .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations